Clinical and Molecular Perspectives of Monogenic Hypertension - Levanovich, Peter E.; Diaczok, Alexander; Rossi, Noreen F. (Current Hypertension Reviews, 2020)
Advances in molecular research techniques have enabled a new frontier in discerning the mechanisms responsible for monogenic diseases. In this review, we discuss the current research on the molecular pathways governing blood pressure disorders with a Mendelian inheritance pattern, each presenting with a unique pathophysiology. Glucocorticoid Remediable Aldosteronism (GRA) and Apparent Mineralocorticoid Excess (AME) are caused by mutations in regulatory enzymes that induce increased production of mineralocorticoids or inhibit degradation of glucocorticoids, respectively. Geller syndrome is due to a point mutation in the hormone responsive element of the promotor for the mineralocorticoid receptor, rendering the receptor susceptible to activation by progesterone, leading to hypertension during pregnancy. Pseudohypoaldosteronism type II (PHA-II), also known as Gordon’s syndrome or familial hyperkalemic hypertension, is a more variable disorder typically characterized by hypertension, high plasma potassium and metabolic acidosis. Mutations in a variety of intracellular enzymes that lead to enhanced sodium reabsorption have been identified. In contrast, hypertension in Liddle’s syndrome, which results from mutations in the Epithelial sodium Channel (ENaC), is associated with low plasma potassium and metabolic alkalosis. In Liddle’s syndrome, truncation of one the ENaC protein subunits removes a binding site necessary protein for ubiquitination and degradation, thereby promoting accumulation along the apical membrane and enhanced sodium reabsorption. The myriad effects due to mutation in phosphodiesterase 3A (PDE3A) lead to severe hypertension underlying sodium-independent autosomal dominant hypertension with brachydactyly. How mutations in PDE3A result in the phenotypic features of this disorder are discussed. Understanding the pathologies of these monogenic hypertensive disorders may provide insight into the causes of the more prevalent essential hypertension and new avenues to unravel the complexities of blood pressure regulation.
Keywords: PDE3A